2020
DOI: 10.1093/pcp/pcaa104
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Metabolism and Signaling: Targets for Improving Agronomic Performance of Crops

Abstract: Gibberellins (GAs) are a class of tetracyclic diterpenoid phytohormones that regulate many aspects of plant development, including seed germination, stem elongation, leaf expansion, pollen maturation, and the development of flowers, fruits, and seeds. During the past years, the primary objective in crop breeding programs has been to increase productivity or yields. “Green revolution” genes that can produce semi-dwarf, high yielding crops were identified as GA synthesis or response genes, confirming the value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 124 publications
1
43
0
Order By: Relevance
“…Values for nitrogen‐use efficiency strongly depend on the amount of plant‐available N. With increasing N application not only a decrease in N‐uptake efficiency was observed, but also a successive decline in N‐utilization efficiency (Barbieri et al., 2008; Gao & Chu, 2020; Haegele et al., 2013; Liao et al., 2012; O’Neill et al., 2004; Wang et al., 2020). In contrast to nitrogen‐use efficiency, information about P‐ and K‐use efficiencies is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Values for nitrogen‐use efficiency strongly depend on the amount of plant‐available N. With increasing N application not only a decrease in N‐uptake efficiency was observed, but also a successive decline in N‐utilization efficiency (Barbieri et al., 2008; Gao & Chu, 2020; Haegele et al., 2013; Liao et al., 2012; O’Neill et al., 2004; Wang et al., 2020). In contrast to nitrogen‐use efficiency, information about P‐ and K‐use efficiencies is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Gibberellins belongs to a large group of tetracyclic diterpenoid carboxylic acid derivatives which have various physiological functions, such as stimulating organ growth through enhancement of cell division and cell elongation [ 151 , 152 ]. Gibberellic acid (GA) is the most common form of gibberellin [ 153 , 154 , 155 ].…”
Section: Effects Of Plant Growth Regulators On Plant Performance Under Saline Conditionsmentioning
confidence: 99%
“…Consequently, disruption in auxin synthesis or auxin transport results in fewer rachis branches and reduced GNPP in rice [ 12 , 13 , 14 ]. GA can affect panicle-associated traits including panicle length, rachis branch number and GNPP in rice [ 15 ]. A previous study demonstrated that OsCYP71D8L controls panicle-related traits by regulating GA homeostasis.…”
Section: Panicle Development and Gnpp Determination In Ricementioning
confidence: 99%